Polarisasi Politik Antara Kepala Desa dengan Penyelenggara Pemilu: Studi Kasus Pemilu 2024 di Bangkalan - Ahmad Sukron (Brawijaya University, 2024)
This research aims to explore the process of political polarization between village heads and election organizers in Bangkalan Regency in the 2024 elections. Through this research, researchers want to explore how factors such as traditional patronage at the village level can create polarization of interests both in the process of forming PPS, KPPS and PKD, PTPS which boils down to personal interests and group interests. The research method used in this research is a qualitative approach with a case study through interview techniques, observation and documentation studies. The results of this study show that political polarization between village heads and election organizers. Vulnerability to political intervention has occurred in Bangkalan Regency, and efforts to avoid it require complex steps. To minimize the problem, several strategic efforts are needed, namely: a) Increasing the awareness of all parties involved. b) Maximizing the role of the village head in carrying out his duties as a policy maker at the village level, c) Increasing public participation and awareness of elections. With the implementation of these measures, the integrity of elections can be improved and public confidence in election results can be maintained.